Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Connect with professionals on our platform to receive accurate answers to your questions quickly and efficiently. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Let's find [tex]\( f(-5) \)[/tex], [tex]\( f(-2) \)[/tex], and [tex]\( f(1) \)[/tex] using the given piecewise function:
[tex]\[ f(x)=\left\{\begin{array}{ll} 4 & \text{if } x < -2 \\ (x+1)^2 - 1 & \text{if } -2 \leq x \leq 2 \\ \frac{1}{2} x - 2 & \text{if } x > 2 \end{array}\right. \][/tex]
1. To find [tex]\( f(-5) \)[/tex]:
[tex]\(-5\)[/tex] is less than [tex]\(-2\)[/tex], so we use the first piece of the definition:
[tex]\[ f(x) = 4 \][/tex]
Thus,
[tex]\[ f(-5) = 4 \][/tex]
So,
[tex]\[ f(-5) = 4 \][/tex]
2. To find [tex]\( f(-2) \)[/tex]:
[tex]\(-2\)[/tex] is between [tex]\(-2\)[/tex] and [tex]\(2\)[/tex], inclusive, so we use the second piece of the definition:
[tex]\[ f(x) = (x+1)^2 - 1 \][/tex]
Thus, substituting [tex]\( x = -2 \)[/tex],
[tex]\[ f(-2) = ((-2)+1)^2 - 1 \][/tex]
[tex]\[ = (-1)^2 - 1 \][/tex]
[tex]\[ = 1 - 1 \][/tex]
[tex]\[ = 0 \][/tex]
So,
[tex]\[ f(-2) = 0 \][/tex]
3. To find [tex]\( f(1) \)[/tex]:
[tex]\(1\)[/tex] is between [tex]\(-2\)[/tex] and [tex]\(2\)[/tex], so again we use the second piece of the definition:
[tex]\[ f(x) = (x+1)^2 - 1 \][/tex]
Thus, substituting [tex]\( x = 1 \)[/tex],
[tex]\[ f(1) = (1+1)^2 - 1 \][/tex]
[tex]\[ = 2^2 - 1 \][/tex]
[tex]\[ = 4 - 1 \][/tex]
[tex]\[ = 3 \][/tex]
So,
[tex]\[ f(1) = 3 \][/tex]
In summary, the values are:
[tex]\[ f(-5) = 4 \][/tex]
[tex]\[ f(-2) = 0 \][/tex]
[tex]\[ f(1) = 3 \][/tex]
[tex]\[ f(x)=\left\{\begin{array}{ll} 4 & \text{if } x < -2 \\ (x+1)^2 - 1 & \text{if } -2 \leq x \leq 2 \\ \frac{1}{2} x - 2 & \text{if } x > 2 \end{array}\right. \][/tex]
1. To find [tex]\( f(-5) \)[/tex]:
[tex]\(-5\)[/tex] is less than [tex]\(-2\)[/tex], so we use the first piece of the definition:
[tex]\[ f(x) = 4 \][/tex]
Thus,
[tex]\[ f(-5) = 4 \][/tex]
So,
[tex]\[ f(-5) = 4 \][/tex]
2. To find [tex]\( f(-2) \)[/tex]:
[tex]\(-2\)[/tex] is between [tex]\(-2\)[/tex] and [tex]\(2\)[/tex], inclusive, so we use the second piece of the definition:
[tex]\[ f(x) = (x+1)^2 - 1 \][/tex]
Thus, substituting [tex]\( x = -2 \)[/tex],
[tex]\[ f(-2) = ((-2)+1)^2 - 1 \][/tex]
[tex]\[ = (-1)^2 - 1 \][/tex]
[tex]\[ = 1 - 1 \][/tex]
[tex]\[ = 0 \][/tex]
So,
[tex]\[ f(-2) = 0 \][/tex]
3. To find [tex]\( f(1) \)[/tex]:
[tex]\(1\)[/tex] is between [tex]\(-2\)[/tex] and [tex]\(2\)[/tex], so again we use the second piece of the definition:
[tex]\[ f(x) = (x+1)^2 - 1 \][/tex]
Thus, substituting [tex]\( x = 1 \)[/tex],
[tex]\[ f(1) = (1+1)^2 - 1 \][/tex]
[tex]\[ = 2^2 - 1 \][/tex]
[tex]\[ = 4 - 1 \][/tex]
[tex]\[ = 3 \][/tex]
So,
[tex]\[ f(1) = 3 \][/tex]
In summary, the values are:
[tex]\[ f(-5) = 4 \][/tex]
[tex]\[ f(-2) = 0 \][/tex]
[tex]\[ f(1) = 3 \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.